As estratégias de correção sob perspectiva da gramática discursivo-funcional - Vivan, Jaqueline [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Considerando a correção como uma espécie de reformulação de um enunciado anterior (cf. FÁVERO, 1999), este trabalho tem por objetivo verificar os diferentes tipos de estratégias de correção presentes na conversação em espanhol e os contextos em que essa reformulação pode servir à expressão da (des)cortesia linguística. Para tanto, analisaremos as ocorrências de correção em dados do espanhol peninsular falado encontradas nas entrevistas orais do PRESEEA (Proyecto para el estudio sociolingüístico del español de España y de América), pertencentes às cidades espanholas de Granada e de Valência. Consideramos que as estratégias de correção podem se relacionar com a cortesia, na medida em que procuram facilitar a interação entre falante e ouvinte e dar prosseguimento à conversação, evitando conflitos entre os interlocutores, conforme previsto por Alvarez (2002). Por outro lado, a correção também pode servir à expressão da descortesia, quando é feita de maneira mais incisiva e menos polida. A pesquisa realizada, de natureza funcionalista, apoia-se no modelo teórico da Gramática Discursivo-Funcional (GDF), proposto por Hengeveld e Mackenzie (2008), que prevê uma integração entre quatro níveis diferentes de análise, hierarquicamente organizados: o Nível Interpessoal (destinado à pragmática), o Nível Representacional (destinado à semântica), o Nível Morfossintático e o Nível Fonológico. Dentro desse modelo, a correção tem sido descrita como função retórica que atua no Nível Interpessoal, o qual, segundo Keizer (2015), trata das atitudes tomadas pelo falante para realizar sua intenção comunicativa. No presente trabalho, também procuramos explicitar as diferenças entre correção e esclarecimento e a relação de ambas as estratégias com as funções retóricas previstas por Keizer (2020).

Considering correction as a kind of reformulation of a previous utterance (cf. FÁVERO, 1999), this work aims to describe and analyze the different types of correction in spoken Peninsular Spanish in order to verify the role they play in communication and how they can contribute to the interaction between the participants of the interaction. In order to perform the analysis, we start from the treatment given to correction within a textualinteractive perspective and verify how the cases we conceive as correction can be described within the functionalist theoretical model of Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008), which underlies our research proposal and consists of four hierarchical analysis levels: the Interpersonal (pragmatic) Level, the Representational (semantic) Level, the Morphosyntactic Level and the Phonological Level. The more general objective of the research unfolds in more specific objectives, such as (i) establishing the characteristics that distinguish correction from other strategies eventually marked by the reformulation or replacement of a previous element, such as paraphrase and hesitation; (ii) verifying whether the cases commonly treated as correction within the textual-interactive perspective can be treated as a rhetorical function in the Functional Discourse Grammar model; (iii) verifying, among the cases that are configured as a rhetorical function at the Interpersonal Level, whether there is any distinction between the rhetorical function Correction and the rhetorical function Clarification, based on the rhetorical functions predicted by Hengeveld and Mackenzie (2008) and refined by Keizer (2020). By associating correction with face-saving strategies, we also intend (iv) to verify in which contexts correction strategies can protect or damage the image of interaction participants, acting as an expression of linguistic politeness or discourtesy. In order to perform the analysis, we adopted a corpus composed of oral interviews from the PRESEEA Project (Proyecto para el estudio sociolingüístico del español de España y de América), from the Spanish cities of Granada and Valência.
Correction strategies from the perspective of discursive-functional grammar
Keywords: Correção; Gramática discursivo-funcional; Espanhol; Correction; Functional discourse grammar; Spoken spanish